2021
DOI: 10.3390/ijms222111307
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Antimicrobial Efficacy of N-Acetyl-l-Cysteine, Rhamnolipids, and Usnic Acid—Novel Approaches to Fight Food-Borne Pathogens

Abstract: In the food industry, the increasing antimicrobial resistance of food-borne pathogens to conventional sanitizers poses the risk of food contamination and a decrease in product quality and safety. Therefore, we explored alternative antimicrobials N-acetyl-L-cysteine (NAC), rhamnolipids (RLs), and usnic acid (UA) as a novel approach to prevent biofilm formation and reduce existing biofilms formed by important food-borne pathogens (three strains of Salmonella enterica and two strains of Escherichia coli, Listeria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Although Gram-positive bacteria had lower MIC (<5 mg/mL) compared to Gram-negative bacteria (≥7.5 mg/mL), no statistically significant difference was found between these two groups of bacteria. Chlumsky et al also concluded that the antimicrobial and antibiofilm effects of NAC are not related to cell wall structure, as NAC inhibits both Gram-positive and Gram-negative bacteria [28].…”
Section: Discussionmentioning
confidence: 99%
“…Although Gram-positive bacteria had lower MIC (<5 mg/mL) compared to Gram-negative bacteria (≥7.5 mg/mL), no statistically significant difference was found between these two groups of bacteria. Chlumsky et al also concluded that the antimicrobial and antibiofilm effects of NAC are not related to cell wall structure, as NAC inhibits both Gram-positive and Gram-negative bacteria [28].…”
Section: Discussionmentioning
confidence: 99%
“…Recently use of NAC as an antibacterial and antibiofilm agent has gained tremendous interest. Some studies have successfully used NAC to demonstrate its in vitro efficacy against planktonically grown as well as biofilms of laboratory strains of bacteria (Li et al, 2020; Aiyer et al, 2021; Chlumsky et al, 2021; Tenório et al, 2021). The antibiofilm activity of NAC is attributed to different aspects such as inhibition of EPS production, bacterial adhesion inhibition, competitive inhibition of cysteine in bacteria, interaction with bacterial proteins via thiol groups, and liquification of biofilm matrix (Zhao et al, 2010; Costa et al,2017; Manoharan et al,2020; Guerini et al,2020; Guerini et al, 2022).…”
Section: Discussionmentioning
confidence: 99%